Findings from Evaluations of Policy-Based Guarantees - Independent Evaluation Group (World Bank, Washington, DC, 2016)
This paper is a survey of practices and results that have been observed in the implementation of PBGs, drawing largely upon four in-depth Project Performance Assessment Reports undertaken by IEG, in Serbia, Macedonia, and Montenegro. It also draws upon IEG’s evaluations of Ghana’s Poverty Reduction Support Credits, which provide background material on the 2015 Ghana PBG. A recent World Bank review of the Albania PBG was also taken into consideration. The report draws on IEG’s technical analyses, coordinated with relevant units of the World Bank and, finally, interviews with a cross-section of World Bank staff. It therefore represents an initial step in building greater awareness of a relatively new and important tool in development finance.